(untitled) (Journal of Small Business Strategy (archive only), 2018)
The internationalization of family firms has increasingly been recognized as an important field of inquiry for international business scholars. And yet, there is a noticeable paucity of original research on key issues, including the differences in antecedents of international performance between family and non-family firms. By drawing on the revised Uppsala model of internationalization from 2009 and the concept of socio-emotional wealth, the present study applies Fuzzy Set Qualitative Comparative Analysis as a methodological approach to identify different configurational sets of antecedents for international performance. Our results suggest that differences in causal configurations of certain antecedents (education, international market knowledge, international business experience, and collaboration intensity) between family and non-family firms exist. Furthermore, we found that the specific characteristics of family firms explain these differences.